2016
DOI: 10.1016/j.ijscr.2016.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Multiple ectopic calcifications in subcutaneous tissues with chronic renal failure: A case report

Abstract: HighlightsMultiple tumor-like ectopic calcifications is a rare syndrome.Complete excisions of the ectopic calcifications were performed, without signs of recurrence in the same sites at follow-up.Incomplete excision of the ectopic calcification in the right shoulder resulted in recurrence in the same site.Subtotal parathyroidectomy with parathyroid autotransplantation appeared not to inhibit the recurrence of ectopic calcification in patients with CRF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Longer treatment duration might lead to formation of calcium hydroxyapatite crystals surrounded by connective tissue composed of fibroblasts and compressed collagen fibers, which is hardly absorbed. This hypothesis was borne out by histological evaluation in our study and in previous studies [8, 15]. (3) Increased pre-operative serum hs-CRP levels and reduced postoperative serum phosphate levels.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Longer treatment duration might lead to formation of calcium hydroxyapatite crystals surrounded by connective tissue composed of fibroblasts and compressed collagen fibers, which is hardly absorbed. This hypothesis was borne out by histological evaluation in our study and in previous studies [8, 15]. (3) Increased pre-operative serum hs-CRP levels and reduced postoperative serum phosphate levels.…”
Section: Discussionsupporting
confidence: 74%
“…According to rare case reports, PTX is considered an effective treatment for TC in hemodialysis patients with SHPT [7, 9]. However, hormone deprivation therapy based on successful PTX did not succeed in shrinking TC in some patients [8]. The reasons for these different clinical regressions have not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that the PTX effectiveness rate for the treatment of UTC was 62.5% and that the non-absorption of UTC after PTX was related to a history of lower ALP levels and UTC. Zhang et al [24] believed that prolonged persistence of UTC induced more fibroblasts and collagen encasing around calcium hydroxyapatite crystals, and this was one of the reasons why the calcinosis was difficult to absorb after PTX. Bas et al [25] found that macrophages were associated with mineralised resorption and those macrophages could transform into osteoclasts and degrade calcified elastin.…”
Section: Discussionmentioning
confidence: 99%